Does the Integrated Health Post have Contextual Effect on Tertiary Preventive Behavior among Hypertensive Patients? A Multilevel Analysis Evidence from Surakarta - Angga Ferdianto; Didik Gunawan Tamtomo; Endang Sutisna Sulaeman (Journal of Health Promotion and Behavior, 2019)
Background: The Indonesian Ministry of Health has launched a community-based non-communicable disease (PTM) control program through the non-communicable disease Integrated Development Post (Posbindu PTM). One of the non-communicable disease which is a very serious health problem is hypertension which is called the silent killer. The purpose of this study was to analyze the contextual effect of integrated development posts on the tertiary prevention behavior of patients with hypertension using Theory of Planned Behavior.Subjects and Method: A cross sectional study was conducted at 25 integrated health post in Surakarta, from September to October 2019. A sample of 200 hipertensive patients was selected by stratified random sampling. The dependent variable was tertiary prevention behavior. The independent variables were education, attitude, subjective norm, perceived behavior control, intention, cadre support, and peer support. The data were collected by questionnaire and analyzed by multiple logistic regression run on Stata 13.Results: Tertiary prevention behavior in patients with hypertention increased with education level ≥Senior high school (b= 1.22; 95% CI= 0.37 to 2.08; p= 0.005), positive attitude (b= 1.51; 95% CI= 0.54 to 2.48; p= 0.002), supportive subjective norm (b= 1.38; 95% CI= 0.46 to 2.29; p= 0.003), strong perceived behavioral control (b= 1.10; 95% CI= 0.17 to 2.03; p= 0.020), strong intention (b= 0.97; 95% CI= 0.13 to 1.82; p= 0.023), strong integrated development post cadre support (b= 1.57; 95% CI= 0.69 to 2.46; p<0.001), and strong peer support (b= 1.46; CI 95% = 0.57 to 2.35; p = 0.001). Integrated development post had a contextual effect on tertiary prevention behavior of hypertension with intra-class correlation (ICC)= 16.03%Conclusion: Education, attitude, subjective norm, perceived behavior control, intention, cadre support, and peer support increased tertiary prevention behavior of hypertension.Keywords: Tertiary prevention of hypertension, Theory of Planned BehaviorCorrespondence: Angga Ferdianto, Institute of Health Science Ngudia Husada Madura, Jl. RE. Martadinata No. 45 Mlajah, Bangkalan 69116. East Java, Indonesia. Email: angga.rmd@gmail.com. Mobile: +6285746555354Journal of Health Promotion and Behavior (2019), 4(3): 224-234https://doi.org/10.26911/thejhpb.2019.04.03.07